The Baylan in Modern Detective Fiction: The Rise of a Precolonial Character in Postcolonial Time - Ruth Clare Garde Torres (Journal of Language and Literature, 2025)
This research combines the conventions set by Jeremy Black and Francisco Demetrio on Detective fiction and the Philippine shaman,  setting them against Ana Micaela Chua’s ideas on Alternative epistemologies. Using these conventions as a means to  analyze selected stories in  Jonathan A. Baldisimo and Ferdinand Benedict G. Tan’s graphic novel series Trese to establish the characteristics  of the baylan, a new, purely Filipino type of detective.  The study will use Francisco Demetrio’s study on the baylan to set the conventions on this pre-colonial character. Jeremy Black’s study on Sherlock Holmes will be used to establish the traditional detective model. This model  uses logic and reasoning and rejects the supernatural as a solution to the case. Both conventions will be challenged using Ana Micaela Chua’s study on alternative epistemologies which argues that the investigative methods in Trese are not a rejection of logic, but rather an expansion of it. These studies were chosen  to help establish the existence of a purely Filipino detective in the character of Alexandra Trese,  a babaylan madirigma and protagonist detective of the series. The study aims to differentiate the Filipino protagonist detective from the Western Holmes model by analyzing Alexandra Trese and her role as babaylan mandirigma  not only as a new form of protagonist detective but as a postcolonial version of the baylan. The main argument being that by defying the Western model of investigation and being grounded in Filipino culture, the babaylan madirigma  is a new form of protagonist detective unique to the Philippines.